Acid Treatments of Ti-Based Metallic Glasses for Improving Corrosion Resistance in Implant Applications - Nora Fernández-Navas; Viktoriia Shtefan; Martin Hantusch; Annett Gebert (Metals, 2024)
Ti-based bulk metallic glasses are promising materials for metallic bone implants, mainly due to their mechanical biofunctionality. A major drawback is their limited corrosion resistance, with high sensitivity to pitting. Thus, effective surface treatments for these alloys must be developed. This work investigates the electrochemical treatment feasibility of nitric acid (HNO3) solution for two bulk glass-forming alloys. The surface states obtained at different anodic potentials are characterized with electron microscopy and Auger electron spectroscopy. The corrosion behavior of the treated glassy alloys is analyzed via comparison to non-treated states in phosphate-buffered saline solution (PBS) at 37 °C. For the glassy Ti47Zr7.5Cu38Fe2.5Sn2Si1Ag2 alloy, the pre-treatment causes pseudo-dealloying, with a transformation from naturally passivated surfaces to Ti- and Zr-oxide nanoporous layers and Cu-species removal from the near-surface regions. This results in effective suppression of chloride-induced pitting in PBS. The glassy Ti40Zr10Cu34Pd14Sn2 alloy shows lower free corrosion activity in HNO3 and PBS due to Pd stabilizing its strong passivity. However, this alloy undergoes pitting under anodic conditions. Surface pre-treatment results in Cu depletion but causes enrichment of Pd species and non-homogeneous surface oxidation. Therefore, for this glassy alloy, pitting cannot be completely inhibited in PBS. Concluding, anodic treatments in HNO3 are more suitable for Pd-free glassy Ti-based alloys.